Treatment outcomes for Hodgkin lymphoma: First report from the Brazilian Prospective Registry. Issue 1 (23rd June 2017) - Biasoli, Irene; Castro, Nelson; Delamain, Marcia; Silveira, Talita; Farley, James; Simões, Belinda Pinto; Solza, Cristiana; Praxedes, Monica; Baiocchi, Otávio; Gaiolla, Rafael; Franceschi, Fernanda; Sola, Caroline Bonamin; et al.
Abstract: Data about Hodgkin lymphoma (HL) in developing countries are scarce and suggest the existence of substantial disparities in healthcare and outcomes in large areas of the world. In 2009, a prospective registry of HL was implemented in Brazil. Web‐based data were contributed by 20 institutions across the country participating in the Brazilian Prospective Hodgkin's Lymphoma Registry. The aim of this study was to present the clinical features and outcomes of newly diagnosed patients with HL aged 13 to 90 years. Multivariate Cox regression models were used to estimate progression‐free (PFS) and overall survival (OS) by clinical factors . A total of 674 patients with classical HL were analysed, with a median follow‐up of 37 months. Median age was 30 years (13‐90). The median time from the onset of symptoms to diagnosis was 6 months (0‐60). Only 6% of patients had early favourable disease, while 65% had advanced disease. Stage IVB was present in 26% and a high‐risk International Prognostic Score in 38%. Doxorubicin, bleomycin, vinblastine, and dacarbazine was used in 93%. The median dose of radiotherapy was 36 Gy for localized disease and 32 Gy for advanced disease. The 3 year PFS in early favourable, early unfavourable, and advanced disease were 95%, 88%, and 66%, respectively. High‐risk International Prognostic Score, advanced disease, and age greater than or equal to 60 were independently associated with poorer PFS and OS; performance status greater than or equal to 2 was also associated with a poorer OS. Poor‐risk patients predominated. Radiation doses for localized disease appear higher than current recommendations. Outcomes appear inferior in developing countries than in developed countries. Delayed diagnosis is probably a major factor underlying these findings. Scattered reports from developing nations suggest that many aspects of standard care in developed countries remain unmet needs for populations living in developing countries. The present report contributes to this body of data, with a proper description of what is currently achieved in urban areas in Brazil.